2009
DOI: 10.1002/ajim.20723
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of occupational health problems from a developed to a developing country: Lessons from the Japan–South Korea experience

Abstract: Many corporations move their manufacturing facilities or technologies from developed to developing countries. Stringent regulations have made it costly for industries to operate in developed, industrialized countries. In addition, labor costs are high in these countries, and there is increasing awareness among the general public of the health risks associated with industry. The relocation of hazardous industries to developing countries is driven by economic considerations: high unemployment, a cheaper labor fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The Korean company might have prevented the outbreak by assuming that the new chemical was toxic even though it did not have any established toxicities at the time. After the outbreak, we reviewed the periodic medical records of Japanese workers exposed to 2-bromopropane and found that mild anemia, which went unnoticed by medical personnel, had occurred in three workers (2). In addition, Ichihara et al (22) found a possible association between hematological indices and individual exposure to 2-bromopropane in workers at a Chinese factory that produced the chemical, although they did not observe cases of severe reproductive toxicity similar to those seen in the Korean workers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Korean company might have prevented the outbreak by assuming that the new chemical was toxic even though it did not have any established toxicities at the time. After the outbreak, we reviewed the periodic medical records of Japanese workers exposed to 2-bromopropane and found that mild anemia, which went unnoticed by medical personnel, had occurred in three workers (2). In addition, Ichihara et al (22) found a possible association between hematological indices and individual exposure to 2-bromopropane in workers at a Chinese factory that produced the chemical, although they did not observe cases of severe reproductive toxicity similar to those seen in the Korean workers.…”
Section: Resultsmentioning
confidence: 99%
“…Many toxic chemicals are widely used in these industries. New chemicals and industries have occasionally been transferred to Korea from Japan (2). …”
Section: Introductionmentioning
confidence: 99%
“…By the end of 2004, 910 workers had been compensated for carbon disulfide poisoning 8. In 1964, used rayon manufacturing machinery that had been made by the Toray Company (Toyo Rayon) of Japan in 1956 was brought into the factory,4 which led to the use of carbon disulfide in the spinning process at the factory.…”
Section: Clinical Manifestations and Toxicological Implications Of Mamentioning
confidence: 99%
“…South Korea has experienced rapid economic development since the 1960s, a phenomenon that has caused the Korean economy to shift from labor-intensive (i.e., light) industries to machinery-intensive (i.e., heavy) industries such as automobile, petrochemical, shipbuilding, nonferrous metal, machinery, and se miconductor industries,4 in which neurotoxic chemicals are widely used. Most of the carbon disulfide poisoning cases that occurred in Korea in the 1980s presented with severe neurologic disturbances 5.…”
Section: Introductionmentioning
confidence: 99%
“…And more than 1,000 workers were certified as carbon disulfide poisoning till 2000. The plant was closed in Korea and transferred to China in 1994 [3][4][5] . Disparities in occupational health services for workers between developed countries and developing countries, and also between large-scale enterprises and small-scale ones should be reduced for occupational health for all as the slogan of ICOH.…”
mentioning
confidence: 99%